Improving the Performance and Knowledge Retention of Aircraft Maintenance Engineering Students in the Theory of Flight through STAD Cooperative Learning - Ak Umairulazmi Pg Abd Mokmin; Jabaidah Bungsu; Masitah Shahrill (Universitas Pendidikan Indonesia (UPI), 2023)
This study used a mixed-method design and an action research approach to investigate the effectiveness of the Student Teams Achievement Division (STAD) in improving 11 TVET students’ performance in the theory of flight. The results of the paired sample t-test revealed that students’ performance improved and were able to retain their knowledge after the STAD intervention. The students reported positive perceptions about STAD cooperative learning after the interview analysis. It encouraged student-centered and active learning, participation, and the development of teamwork skills. The discussion and practical and collaborative activities helped the students to retain their knowledge since they formed mental images of what they learned. This study concluded that STAD cooperative learning can be a helpful tool in improving TVET students’ performance in the theory of flight. This is more achievable when it is conducted in a teacher-friendly and well-prepared classroom environment. Implications of the findings in TVET and suggestions of effective ways to implement STAD cooperative learning are discussed.